Team Processes Factors Affect Team Effectiveness of Tertiary Students: A Survey Research at UNIMAS - Tan, Liew Tin (Universiti Malaysia Sarawak, (UNIMAS), 2009)
This research is study on the team processes factors that affect the team effectiveness among university student in Universiti Malaysia Sarawak (UNIMAS), Kota Samarahan. The team processes factors that affect the team effectiveness of tertiary students are communication, team decision making and conflict management. The methodology used in this research is the survey method using survey research questionnaires as the instrument. A total of 350 students were used as samples in this study. The results of Pearson Correlation Analysis and Multiple Regression are used in this research In addition, the findings of this research is beneficial for the students and future researchers to determine the team processes factors that affect the team effectiveness of tertiary student and to identify method of improving and enhancing the practice of effective teamwork in the university and workplace.